Edukasi dalam Pengelolaan Sampah Rumah Tangga Secara 3R (Reduce, Reuse, Recycle) di Desa Poto - Desy Fadilah Adina Putri; Abdul Hamid; Nadia R. Kaleka; Evi Rosmiana (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
The presence of scattered waste in the environment has a significant impact on both environmental sustainability and human health. In Indonesia, the accumulation of waste has reached alarming levels, amounting to approximately 175,000 tons per day, or the equivalent of 64 million tons annually. Household activities are one of the main contributors, producing a wide variety of waste, including organic and non-organic materials. Poto Village is among the areas receiving particular attention regarding this issue due to the challenges it faces in waste management. Improper management of waste not only leads to air, water, and soil pollution but also increases the risk of various health problems within the community. One of the programs designed to address this problem is the 3R program, which emphasizes three main principles: reduce, recycle, and reuse. The purpose of this community service initiative is to improve public knowledge and awareness of effective waste management through the application of 3R practices. The activities were carried out in three main stages, namely preparation, education, and discussion through a question-and-answer session. The process began with a socialization activity that introduced the objectives, purposes, and sustainability aspects of waste management efforts in the village. The educational session was attended by 30 participants, consisting of housewives, farmers, and entrepreneurs, who represented key groups within the community. Furthermore, interviews with local cadres revealed that waste is collected weekly by garbage trucks, indicating the village’s commitment to environmental management. Participants responded enthusiastically throughout the educational sessions, showing a strong interest and positive reception toward the information provided. As a follow-up step, future activities could include hands-on training in waste management using available media and tools, which would allow participants to apply the concepts learned in a practical and sustainable manner.